DAMPAK FLUKTUASI INFLASI TERHADAP PERUBAHAN HARGA SAHAM : Studi Pada Perusahaan Sektor Perbankan Yang Listing Di Bursa Efek Indonesia - Etus Saputra; Yuniarti Yuniarti (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Ilmu Ekonomi (STIE) Pontianak, 2023)
The purpose of this study is to determine the impact of inflation fluctuations on stock price changes in the banking sector. Sample collection using purposive sampling technique with the condition that the sample is a company listed on the Indonesia Stock Exchange and publishes complete financial statements in the research period from 2019 - 2021, so that 24 companies were collected and a sample of 72 financial statement data was obtained. Data analysis techniques using the help of Eviews version 10, which shows the following results; based on LM test with probability results 0,14 > 0,05 which means that the right model estimation is the common effect model; from the heterokedastis test obtained probability value 0,76 > 0,05 means that heterokedastis does not occur, and normality test 0,94 > 0,05 this means that the residual is normally distributed; and the significance value of the hypothesis test is 0.9162 > 0,05 this means that fluctuations in inflation did not have a significant impact on changes in share prices of banking sector companies listed on the Indonesia Stock Exchange during the three study periods. Key word: fluctuations in inflation, changes in stock prices, banking sector